Handbook of environmental fluid dynamics : (Taylor & Francis, 2013)
The handbook features 81 chapters written by 135 renowned researchers from around the world. Covering environmental, policy, biological, and chemical aspects, it tackles important cross-disciplinary topics such as sustainability, ecology, pollution, micrometeorology, and limnology.